1998
DOI: 10.1098/rspb.1998.0366
|View full text |Cite
|
Sign up to set email alerts
|

Paternal products and by–products in Drosophila development

Abstract: Tails of fertilizing spermatozoa persist throughout embryogenesis in Drosophila species and can be observed within the midguts of larvae after hatching. Throughout development, sperm proteins slowly di¡use or are stripped from the giant sperm tail residing within the embryo's anterior end. The shape and position of the sperm within the embryo are regulated such that, during organ formation, the unused portion of the sperm is enveloped by the developing midgut. This persistent, paternally derived structure is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 30 publications
2
32
2
Order By: Relevance
“…We deem temperature unlikely a major driving force in our study because temperature was kept constant in our experiments and a temperaturedependent effect, if occurring, should have been observable in both mating directions. An uneven distribution of mtDNA haplotypes could also be caused by a bottleneck effect or by random assortment of large mitochondrial sperm derivates (assuming these contain mtDNA) during early developmental stages (Bergstrom and Pritchard, 1998;Pitnick and Karr, 1998). These are stochastic processes, however, and are thus not in agreement with the observed pair-specific distribution of paternal leakage here.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…We deem temperature unlikely a major driving force in our study because temperature was kept constant in our experiments and a temperaturedependent effect, if occurring, should have been observable in both mating directions. An uneven distribution of mtDNA haplotypes could also be caused by a bottleneck effect or by random assortment of large mitochondrial sperm derivates (assuming these contain mtDNA) during early developmental stages (Bergstrom and Pritchard, 1998;Pitnick and Karr, 1998). These are stochastic processes, however, and are thus not in agreement with the observed pair-specific distribution of paternal leakage here.…”
Section: Discussioncontrasting
confidence: 55%
“…First, the directed sequestration of mitochondrial sperm derivatives into the midgut and subsequent defecation during early embryonic development, a mechanism put forward to exclude paternal mtDNA from inheritance in D. melanogaster and D. pachea (Pitnick and Karr, 1998). A failure of this mechanism could potentially lead to the inclusion of paternal mtDNA within the developing embryo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is ample evidence that the reproductive tract is among the most rapidly evolving of all phenotypic traits (Eberhard 1985(Eberhard , 1996Thomas & Singh 1992;Rice & Holland 1997;Hellriegel & Ward 1998;Pitnick & Karr 1998). Rice (1996), Rice & Holland (1997) and Holland & Rice (1999) showed that, when female evolution is experimentally halted, males actually become toxic to females.…”
Section: Discussionmentioning
confidence: 99%
“…Theory predicts that any advantages in producing such large sperm have little to do with providing resources to the devel oping zygote (Parker, 1982). Indeed Pitnick & Karr (1998) have found that the tails of fertilizing sperm persist throughout embryogenesis in Drosophila species and are sequestered within the midguts of the developing larvae. They are later defecated by the larvae after hatching.…”
Section: Introductionmentioning
confidence: 99%